2018
DOI: 10.1155/2018/2580165
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Robot Arm Using Decoded Joint Angles from Electrocorticograms in Primate

Abstract: Electrocorticogram (ECoG) is a well-known recording method for the less invasive brain machine interface (BMI). Our previous studies have succeeded in predicting muscle activities and arm trajectories from ECoG signals. Despite such successful studies, there still remain solving works for the purpose of realizing an ECoG-based prosthesis. We suggest a neuromuscular interface to control robot using decoded muscle activities and joint angles. We used sparse linear regression to find the best fit between band-pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…Several articles also reported that γ rhythm was useful for 3D hand trajectory (Shimoda et al, 2012) and EMG prediction (Shin et al, 2012) in monkeys. Also, some reports indicated that the δ and γ bands were suitable for decoding arm motion (Chao et al, 2010), arm movement trajectories (Pistohl et al, 2008), grasp force profile (Chen et al, 2013), joint angle and muscle activity (Shin et al, 2018) based on the ECoG. Our results are in good agreement with the previous reports (Chao et al, 2010;Chen et al, 2013;Shin et al, 2012Shin et al, , 2018.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several articles also reported that γ rhythm was useful for 3D hand trajectory (Shimoda et al, 2012) and EMG prediction (Shin et al, 2012) in monkeys. Also, some reports indicated that the δ and γ bands were suitable for decoding arm motion (Chao et al, 2010), arm movement trajectories (Pistohl et al, 2008), grasp force profile (Chen et al, 2013), joint angle and muscle activity (Shin et al, 2018) based on the ECoG. Our results are in good agreement with the previous reports (Chao et al, 2010;Chen et al, 2013;Shin et al, 2012Shin et al, , 2018.…”
Section: Discussionsupporting
confidence: 91%
“…Also, some reports indicated that the δ and γ bands were suitable for decoding arm motion (Chao et al, 2010), arm movement trajectories (Pistohl et al, 2008), grasp force profile (Chen et al, 2013), joint angle and muscle activity (Shin et al, 2018) based on the ECoG. Our results are in good agreement with the previous reports (Chao et al, 2010;Chen et al, 2013;Shin et al, 2012Shin et al, , 2018. Although we identified the ECoG frequency bands with the highest performance, the best overall performance was achieved when all sensorimotor rhythms were considered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other NHP and human epidural datasets have been used to decode two-dimensional position of one arm (Flint et al, 2012;Marathe & Taylor, 2013), the wrist Spüler et al, 2016) or the three-dimensional trajectory of both arms using grids with an IED ranging from 1 to 10 mm. The results of these studies displayed similar, albeit slightly inferior (range of correlation coefficients for epidural r = $0.3-0.7 < subdural r = $0.5-0.9, where the reported r2 scores were translated to r; Table S3), results compared with NHP and human subdural studies that decoded trajectories of the arm (e.g., Nakanishi et al, 2017;Shin et al, 2018;Talakoub et al, 2017) and fingers (e.g., Flint et al, 2020;Xie et al, 2018). Of particular interest is a study from Flint et al (2017) who attempted to directly compare performance between epidural and subdural recordings using both standard clinical and high-density grids (4-mm IED) to decode continuous grasp kinematics.…”
Section: Offline Regression Studiesmentioning
confidence: 81%
“…The missing muscle signals are proposed to be predicted from the remaining muscles using the muscle synergy methods [24][25][26][27]. In our previous works, we developed a method for estimating myoelectric signals and arm trajectories and forces in real time from electrocorticogram (ECoG) [28][29][30][31][32] and control of robotic arms using joint angles and myoelectric signals predicted by ECoG [33]. In patients who are completely deficient and unable to measure sEMG signals, these BMI techniques could control prosthetic hands.…”
Section: Discussionmentioning
confidence: 99%